THE EFFECT OF DIGITAL FINANCE BEHAVIOR TOWARD SHADOW ECONOMY IN SOUTHEAST ASIA COUNTRIES - Sulistiyowati, Liliek Nur; Effrisanti, Yulia (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Digital finance behavior is increasing along with advances in information and communication technology. Digitalization in finance means an increase in the use of digital technology in the work and product development of the banking and financial sector. The purpose of this study is to determine the effect of digital finance behavior on the shadow economy. The study took the object of 6 countries in Southeast Asia, namely Indonesia, Singapore, Malaysia, Thailand, Vietnam and the Philippines. The selection of research objects is based on the consideration that the six countries represent countries in Southeast Asia with a large population and potential broad market. This research uses literature study method. The results of the literature study show that digital financial behavior increases the potential for the shadow economy in Southeast Asian countries.